Mewujudkan Integrasi Nasional Melalui Kesadaran Terhadap Keberagaman di Masyarakat Indonesia - Yunita, Intan; Amaruna, Nofyan Fajry; Anbiya, Bakti Fatwa (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This article is about the importance of diversity awareness in strengthening national integration in Indonesia, with the aim of creating inclusive and sustainable national integration.Â  This article was prepared through a literature study approach, as this method can help to understand the problem in depth in order to find theories. This article identifies the role of diversity awareness, challenges in building such awareness, strategies to raise awareness, and future hopes and challenges. Diversity awareness is needed to strengthen unity within the diversity of Indonesian society. Challenges in building awareness include unequal access to education and information, prejudice and stereotypes, inequality in resource distribution, political and religious polarisation, and the influence of globalisation. Strategies to raise diversity awareness include multicultural education, awareness campaigns through mass and social media, inter-group dialogue, and inclusive policy formation. In the future, the role of individuals and cooperation across sectors and groups is expected to strengthen inclusive and harmonious national integration. In conclusion, awareness and concern for diversity is an important foundation to be able to build a strong and inclusive national integration for the people in Indonesia.